2013
DOI: 10.5603/cj.a2018.0156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air pollution on hospital patients admitted with ST- and non-ST-segment elevation myocardial infarction in heavily polluted cities within the European Union

Abstract: Background: Air pollution triggered diseases have become a leading health problem worldwide. The main adverse effects of air pollutants on human health are related to the cardiovascular system and particularly show an increasing prevalence of myocardial infarct and stroke. The aim of the study was to evaluate the influence of main air pollutants on non-ST-segment elevation myocardial infarction (NSTEMI) and ST-segment elevation myocardial infarction (STEMI) admissions to local interventional cardiology centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…In our study, NO 2 exposure yielded the largest associations with CVD hospitalization for 2013-2015. Larger effects of NO 2 compared to PM were also found for MI hospitalizations (2014)(2015) in the three Polish industrial areas, showing about 29% higher risk (for a 10 µg/m 3 increase) at lag 0, and 26% higher risk at lag 1 [5]. In an Iranian study (2010-2012) carried out in an industrial urban area, a 10 µg/m 3 increase in NO 2 was associated with a 26% higher risk of all-age hospitalization for atrial fibrillation after 24 h, while no significant associations emerged for PM exposure [33].…”
Section: Acute Effects Of Pm On Cvd Hospitalizationsmentioning
confidence: 85%
See 3 more Smart Citations
“…In our study, NO 2 exposure yielded the largest associations with CVD hospitalization for 2013-2015. Larger effects of NO 2 compared to PM were also found for MI hospitalizations (2014)(2015) in the three Polish industrial areas, showing about 29% higher risk (for a 10 µg/m 3 increase) at lag 0, and 26% higher risk at lag 1 [5]. In an Iranian study (2010-2012) carried out in an industrial urban area, a 10 µg/m 3 increase in NO 2 was associated with a 26% higher risk of all-age hospitalization for atrial fibrillation after 24 h, while no significant associations emerged for PM exposure [33].…”
Section: Acute Effects Of Pm On Cvd Hospitalizationsmentioning
confidence: 85%
“…In such a study, the risk of CVD hospitalization increased by 19.6% for a 10 µg/m 3 increase in PM 2.5 (lag 0) [11]. Moreover, a recent case-crossover study (2014)(2015) in highly polluted small/mediumsized industrial cities in southern Poland, reported a 16% increased risk of hospitalization for acute myocardial infarction per 10 µg/m 3 increase in PM 10 , and a 20% increased risk for PM 2.5 (lag 0) [5].…”
Section: Acute Effects Of Pm On Cvd Hospitalizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the source, according to the European Environment Agency, particulate matter contributes to the premature death of approximately 428,000 citizens of Europe every year [2]. There is a great deal of evidence in the literature for the short-and long-term adverse effects of air pollution on the cardiovascular and pulmonary systems [3][4][5][6][7][8][9][10][11][12][13]. The exact mechanisms associated with the impact of air pollution on the human body remain unclear.…”
Section: Introductionmentioning
confidence: 99%